Visuospatial processing in early Alzheimer's disease: A multimodal neuroimaging study. (March 2015) - Jacobs, Heidi I.L.; Gronenschild, Ed H.B.M.; Evers, Elisabeth A.T.; Ramakers, Inez H.G.B.; Hofman, Paul A.M.; Backes, Walter H.; Jolles, Jelle; Verhey, Frans R.J.; Van Boxtel, Martin P.J.
Abstract: Introduction: Dorsal pathway dysfunctions are thought to underlie visuospatial processing problems in Alzheimer disease (AD). Prior studies reported compensatory mechanisms in the dorsal or ventral pathway in response to these functional changes. Since functional and structural connectivity are interrelated, these functional changes could be interpreted as a disconnection between both pathways. To better understand functional alterations in the dorsal pathway, we combined functional imaging with diffusion tensor imaging (DTI) in patients with mild cognitive impairment (MCI), a likely prodromal stage of AD. Methods: Eighteen older male individuals with amnestic MCI (aMCI) and 18 male cognitively healthy individuals, matched for age (range 59–75 years) and education, performed an object recognition task in the Magnetic Resonance Imaging (MRI) scanner. Neural activation was measured during recognition of non-canonically versus canonically oriented objects. Regions showing activation differences between groups were also investigated by DTI. Results: Recognition of non-canonical objects elicited increased frontal, temporal and parietal activation. Combining the functional MRI (fMRI) with the DTI results showed less deactivation in areas with decreased diffusion (mediolateral parietal and orbitofrontal) and increased activation in areas with increased diffusion (parietal and temporal) in aMCI patients. Finally, in aMCI patients decreased diffusion was found in the hippocampal cingulum, connecting both pathways. Conclusions: Our results showed increased activation in early AD patients in ventral and dorsal pathways. A decrease in deactivation and diffusion suggests functional reorganization, while increased activation and diffusion suggests compensatory processes. This is the first study showing structural evidence for functional reorganization, which may be related to connectivity loss in the cingulum.